Role of Mass Media in Dissemination of Agricultural Technology among the Farmers of Jaffarabad District of Balochistan - Inayatullah Memon; Khalid N. Panhwar; Rafique A. Chandio; Abdul Latif Bhutto; Aijaz A. Khooharo (Journal of Basic & Applied Sciences, 2014)
Agricultural extension is essentially a message delivery system organized to convey the latest findings ofagricultural research to farmers. Effective communication is therefore, the prime requirement in extension work. This study conducted during 2013 attempted to examine the role of mass media in dissemination of agricultural technology among the farmers of Jaffarabad district of Balochistan province of Pakistan. The results revealed majority of the respondents were male (80%), belonged to the age group of 31-40 years (45.35%), and with formal education of (31%). Information regarding agricultural farming revealed that three-fourth (75%) of the respondents owned personal land, medium size of farms (12.5-50.0 acres) were more common (52%). Majority (70.93%) of the respondents perceived that the sources of media used in the area are highly conventional. About two third (66.28%) of the respondents perceived that the sources of media for agricultural information was highly accessible. Relative majority of the respondents (40.70%) supposed to prefer listening to agricultural programs between 8 pm to 12.00 am; 33.72% respondents showed preference for listening to agricultural programs from 4.00 -8.00 pm. Majority (70.93%) of the respondents considered the information receiving through mass media is highly relevant in solving agriculture problems. Majority (41.86%) of the respondents reported infrastructural development due to agricultural information received through mass media and 22.09 percent found that agricultural information received through mass media was helpful in capacity building. Regarding major obstacles in receiving information, 31.40 percent respondents reported power failure, followed by high cost (24.42%), and poor signals (12.79%).